2012
DOI: 10.4103/0019-5154.97679
|View full text |Cite
|
Sign up to set email alerts
|

Not just skin deep: A case report of multiple endocrine neoplasia type 1

Abstract: Multiple endrocrine neoplasia (MEN) type 1 is characterized by mainly a triad of pancreatic, pituitary and parathyroid involvement. This is a case report of a 41-year-old male in whom recognition of collagenoma and gingival papule led to the identification of MEN type 1. Often the recognition of such dermatological manifestations help in the presymptomatic diagnosis of complex syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…3,6,11 It has been suggested that the angiofibromas of Wermer syndrome differ from those associated with tuberous sclerosis in that they are smaller, fewer in number, and concentrated on the upper lip and vermilion border. 3,11,12 The genetic aberrations in the two types are clearly different, with MEN-1 angiofibromas exhibiting loss of MEN-1 gene function whereas tuberous sclerosis angiofibromas stem from dysfunction in one of the TS genes. 13 Multiple facial angiofibromas have also been reported as an early manifestation of Birt-Hogg-Dubé syndrome.…”
Section: Discussion Follows On Page 792mentioning
confidence: 99%
See 3 more Smart Citations
“…3,6,11 It has been suggested that the angiofibromas of Wermer syndrome differ from those associated with tuberous sclerosis in that they are smaller, fewer in number, and concentrated on the upper lip and vermilion border. 3,11,12 The genetic aberrations in the two types are clearly different, with MEN-1 angiofibromas exhibiting loss of MEN-1 gene function whereas tuberous sclerosis angiofibromas stem from dysfunction in one of the TS genes. 13 Multiple facial angiofibromas have also been reported as an early manifestation of Birt-Hogg-Dubé syndrome.…”
Section: Discussion Follows On Page 792mentioning
confidence: 99%
“…Several reports about the association between cutaneous lesions (especially angiofibromas and collagenomas) and MEN1 have been published, with the initial observation coming from Darling et al in 1997 . These cutaneous lesions often appear at the first phases of the syndrome and in some cases have facilitated an early diagnosis of MEN1 before internal tumors were detected . Multiple facial angiofibromas are most often associated with tuberous sclerosis, but have been reported in nearly 90% of MEN1 patients .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, café-au-lait macules were seen in 38% of the patients; however, they were not considered to be diagnostically significant [14]. Other manifestations included confetti-like hypopigmented macules (6%) and gingival papules (6%) [15].…”
Section: Skin Manifestationsmentioning
confidence: 96%